2017
DOI: 10.1038/s41598-017-14904-w
|View full text |Cite
|
Sign up to set email alerts
|

The emergent rhizosphere: imaging the development of the porous architecture at the root-soil interface

Abstract: The rhizosphere is the zone of soil influenced by a plant root and is critical for plant health and nutrient acquisition. All below ground resources must pass through this dynamic zone prior to their capture by plant roots. However, researching the undisturbed rhizosphere has proved very challenging. Here we compare the temporal changes to the intact rhizosphere pore structure during the emergence of a developing root system in different soils. High resolution X-ray Computed Tomography (CT) was used to quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
85
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 41 publications
11
85
3
1
Order By: Relevance
“…However, the current study used soil sieved to < 250 μm, whereas previous research used soil sieved to < 2 mm (e.g. Feeney et al ., ; Helliwell et al ., ; Koebernick et al ., ). Our smaller particle size and the resulting packing condition produced a soil environment more typical of intra‐aggregate structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the current study used soil sieved to < 250 μm, whereas previous research used soil sieved to < 2 mm (e.g. Feeney et al ., ; Helliwell et al ., ; Koebernick et al ., ). Our smaller particle size and the resulting packing condition produced a soil environment more typical of intra‐aggregate structure.…”
Section: Discussionmentioning
confidence: 99%
“…The present study confirms previous observations of increased pore volume fraction at the soil–root interface (Helliwell et al ., ; Koebernick et al ., ). The radial porosity distribution about the root surface showed very different patterns for individual replicates suggesting that even in a relatively homogeneous soil there can be very different porosity distributions for individual roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that soil porosity varies with distance from the root surface, with an increased porosity directly adjacent to the root surface (Hinsinger et al, 2005;Helliwell et al, 2017;Koebernick et al, 2019; see also Supporting Information Fig. Recent work has shown that soil porosity varies with distance from the root surface, with an increased porosity directly adjacent to the root surface (Hinsinger et al, 2005;Helliwell et al, 2017;Koebernick et al, 2019; see also Supporting Information Fig.…”
Section: Introductionmentioning
confidence: 96%
“…However, investigation of root morphology in soil is challenging due to its opacity, and investigation of exudation in soil is challenging due to soils physiochemical complexity (Cai et al ., ). Specialized imaging techniques, such as magnetic resonance imaging, computed tomography (Metzner et al ., ; Helliwell et al ., ), or the use of labeled plants (Rellán‐Álvarez et al ., ), have been developed, but they are not widely accessible or amenable to high‐throughput experimentation (Metzner et al ., ). Similarly, approaches for the investigation of root exudation in soils include the use of in situ soil drainage systems (lysimeters) in fields (Strobel, ), which are low throughput and require complex installations, or of laboratory‐based extraction methods that are based on flushing the soil with large volumes of liquids (Swenson et al ., ; Pétriacq et al ., ).…”
Section: Introductionmentioning
confidence: 99%